Metaanálisis de la prevalencia de chlamydia trachomatis entre hombres y mujeres militares (2019)
Introduction: Chlamydia trachomatis is the first cause of sexually transmitted infections in the world. The risk groups are young adults and it is postulated that it is greater in the military and in women. However, the evidence is heterogeneous. Objective: To perform a meta-analysis of the prevalence of Chlamydia trachomatis infection in military men and women. Methods: Systematic review with meta-analysis. Was applied a protocol with criteria for inclusion, exclusion, evaluation of methodological quality and reproducibility. Was calculated the Z-test for difference in proportions, prevalence with their 95 % confidence intervals, prevalence ratios and sensitivity analysis. Results: Were included eleven articles with 108 856 soldiers from eight different countries. The prevalence ranged between 15.4 % (95 % CI 11.6-19.3) and 3.0 % (95 % CI 0.4-0.5). The overall prevalence was 5.5 % (95 % CI 5.3-5.6) with significant differences between men 2.5 % (95 % CI = 2.4-2.7) and women 9.5 % (95 % CI = 9.2-9.7). In the meta-analysis of indirect measures, we found a prevalence ratio of 3.7 (95 % CI = 3.5-3.9) and a difference in proportions of 6.9 (95 % CI = 6.6-7.2). Conclusion: The prevalence of infection in the military is higher than that found in other population groups with a greater proportion in women. There is evidence of the need to implement screening programs at the time of entry into the armed forces, to carry out periodic surveillance and to implement subsequent investigations that study the double vulnerability of the military woman. © 2019, Editorial Ciencias Medicas. All rights reserved.